2010
DOI: 10.1080/10401330903446321
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lecture and a Standardized Patient Encounter on Medical Student Rape Myth Acceptance and Attitudes Toward Screening Patients for a History of Sexual Assault

Abstract: Sexual assault education can diminish rape myth acceptance and promote screening for sexual assault.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Even therapists who work specifically with SA survivors may hold negative perceptions of SA survivors (Ullman, 2014). Importantly, these attitudes are modifiable with education about SA myths and facts (Milone, Burg, Duerson, Hagen, & Pauly, 2010). Societal barriers are challenging to address.…”
Section: Discussionmentioning
confidence: 99%
“…Even therapists who work specifically with SA survivors may hold negative perceptions of SA survivors (Ullman, 2014). Importantly, these attitudes are modifiable with education about SA myths and facts (Milone, Burg, Duerson, Hagen, & Pauly, 2010). Societal barriers are challenging to address.…”
Section: Discussionmentioning
confidence: 99%
“…A review of international post-rape training programmes showed that there were marked differences in the courses offered to providers [7-16], with lengths ranging from a 45 minute lecture to medical students [15] and 2 hours training on clinical forensic medicine in the United States of America (USA) [8], to a 6 month rotation in forensic medicine for emergency room physicians in Australia [13]. The nursing programmes especially the Sexual Assault Nurse Examiner (SANE) programmes in the USA [9,10] and Canada [9,11] were found to be the most established with a 5 – 7 day didactic training programme followed by clinical exposure in a practical setting.…”
Section: Introductionmentioning
confidence: 99%
“…The content of the courses have also varied, with a focus on the examination of survivors and evidence collection. Some of these programmes have reported on improvements in provider knowledge and skills after training but these studies were conducted with small groups in limited settings and did not include a mixed group of providers in a national programme [7,10,15,16]. No studies were found from developing, low resourced settings.…”
Section: Introductionmentioning
confidence: 99%
“…Potential barriers to screening, including prejudicial or false beliefs about sexual assault, survivors, and perpetrators, should be addressed. One related study of medical students indicated that sexual assault education can diminish prejudicial or false attitudes about rape and promote screening for sexual assault [26].…”
Section: Additional Training For Campus Leadersmentioning
confidence: 99%